Long-Term Fiscal Risks and Sustainability in an Oil-Rich Country : The Case of Russia - Bogetic, Zeljko (2012)
Russia entered the global crisis with strong fiscal position, low public debt, and large fiscal and monetary reserves, which helped it cushion the crisis shocks. But the rise in the non-oil fiscal deficit in 2007-08 and, more importantly, the massive impact of the global crisis in late 2008 and 2009 have dramatically altered Russia's medium-term and long-term economic and fiscal outlook. While Russia is emerging from this crisis on a much stronger footing than during the 1998-09 crisis thanks to its strong-pre crisis fundamentals, large fiscal reserves and solid management of the crisis, it will nevertheless need to implement sustained fiscal adjustment in the coming years. Both revenue and expenditure measures will be needed. This will require 2-3 percentage points of GDP in fiscal adjustment for about five years in addition to keeping total expenditure levels at a relatively low 31.5 percent of GDP, consistent with long-term social expenditure needs and requirements of long-term fiscal sustainability. Following a period of adjustment, if Russia would restrain its long-term non-oil deficits to the permanent income (PI) equivalent of its oil revenues as proposed in this paper, its fiscal policy will return to long-term sustainable path. The long-term, sustainable level of non-oil fiscal deficit is estimated at about 4.3 percent of GDP. With the 2009 actual non-oil fiscal deficit of about 14 percent of GDP, this implies significant and sustained fiscal adjustment over the medium term. The expenditure needs of the social security system as well as a reduction in key non-oil taxes represent a major fiscal risk to all scenarios.